FROM “MARRIAGE IS SCARRY” TO THE READINESS GAP: GEN Z’S MARRIAGE ANXIETY AND THE NORMATIVE RESPONSIVENESS OF ISLAMIC FAMILY LAW IN PEKANBARU - Devita Anggraini; Widiya Yul (Program Studi Hukum Keluarga Fakultas Syariah UIN Datokarama Palu, 2026)
Generation Z in the digital era is experiencing a shift in perceptions of marriage, reflected in the “Marriage is Scary” discourse circulating on platforms such as TikTok and Instagram. In this study, the term does not denote rejection of marriage but refers to apprehension expressed through postponement, economic concerns, relational uncertainty, and trauma-related considerations. This study aims to analyze Generation Z’s perceptions of marriage, identify factors contributing to postponement, and examine their conceptual alignment with Book I of the Compilation of Islamic Law (KHI) as Indonesia’s codified Islamic family law. Using a mixed-methods sequential explanatory design, 100 respondents in Pekanbaru were surveyed, followed by thematic analysis and normative legal review. While 78% consider marriage important and 69% intend to marry, 50% report delaying it primarily due to economic factors, alongside partner uncertainty (25%) and trauma (17%). Qualitative findings show that marriage remains viewed as worship and a meaningful life goal, yet increasingly framed through readiness standards. Normative analysis of Articles 15–18 and 80 of the KHI indicates a conceptual divergence between formal legal validity and the economic and psychological readiness emphasized by respondents. This study highlights shifting standards of marital readiness and examines their alignment with existing legal provisions.